A polyamine-modified near-infrared fluorescent probe for selective staining of live cancer cells - König, Sandra G.; Öz, Aliye Simin; Krämer, Roland (Chemical communications, 2015)
We report the synthesis of novel polyamine-modified near-infrared (NIR) probes, which show excellent water-solubility and good optical properties. One probe was taken up efficiently by living cancer cell lines whereas no staining of the non-cancer cells was observed.